2014
DOI: 10.4102/sajems.v17i5.627
|View full text |Cite
|
Sign up to set email alerts
|

The association among the seven elements of the black economic empowerment score and market performance

Abstract: The black economic empowerment (BEE) score consists of seven elements, namely ownership, management control, employment equity, skills development, preferential procurement, enterprise development and socio-economic development. The purpose of this study is to establish whether an association exists between an entity's BEE elements and its share returns in the short term.Based on prior literature, it appears that the market reacts positively to an announcement of a BEE deal, although the literature also indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This relationship was significant for both components. Van der Merwe and Ferreira (2014) found that there was a significant and positive relationship between the management control component and the share return.…”
Section: Bee Shares and Stock Returnsmentioning
confidence: 96%
See 1 more Smart Citation
“…This relationship was significant for both components. Van der Merwe and Ferreira (2014) found that there was a significant and positive relationship between the management control component and the share return.…”
Section: Bee Shares and Stock Returnsmentioning
confidence: 96%
“…Van der Merwe and Ferreira (2014) investigated the relationship between a firm's BEE components and short-term share returns. The study covered the period 2005 to 2011 and the sample comprised top empowerment firms listed by Empowerdex/Financial Mail.…”
Section: Bee Shares and Stock Returnsmentioning
confidence: 99%
“…As a result, directors could have been deterred to engage in share transfer transactions and rather focussed on elements that did not have such a substantial impact on shareholder value. Van der Merwe and Ferreira (2014) found that an increase in B-BBEE element scores was negatively associated with changes in share prices.…”
Section: Changes In the Individual Broad-based Black Economic Empowerment Element Scoresmentioning
confidence: 97%
“…Previous authors focussed on the beneficiaries of B-BBEE (Hoffman, 2008;Patel & Graham, 2012). Others explored the relationship between B-BBEE scores and share market performance (Chipeta & Vokwana, 2011;De Villiers & Ferreira, 2011;Jackson, Allesandri, & Black, 2005;Mehta & Ward, 2017;Strydom, Christison, & Matias, 2009;Van der Merwe & Ferreira, 2014;Ward & Muller, 2010;Wolmarans & Sartorius, 2009) and other financial performance measures (Acemoglu et al, 2007;Kleynhans & Kruger, 2014;Mathura, 2009;Morris, 2018). As far as it could be established, no authors empirically investigated trends in B-BBEE compliance by accounting for changes in the total B-BBEE and element scores.…”
Section: Introduction and Motivation For The Studymentioning
confidence: 99%
“…Apart from the social justice and legitimacy perspectives, South African and foreign companies are increasingly questioning whether there is a clear financial motivation to comply and improve compliance with the 2003 Act (De Wet 2016; Kleynhans & Kruger 2014). Contradictory results have been reported on the relationship between B-BBEE and financial performance in previous studies (Acemoglu et al 2007;Kleynhans & Kruger 2014;Mathura 2009;Morris 2018;Van der Merwe & Ferreira 2014). It should, however, be noted that these authors utilised relatively small samples, mainly employed accounting-based and market-based performance measures and, with the exception of Morris (2018) and Van der Merwe and Ferreira (2014), focused on total B-BBEE scores without accounting for the individual elements of the scorecard.…”
Section: Introductionmentioning
confidence: 99%